Researches on energy conversion of municipal waste by plasma decomposition for energy-efficiency in civil engineering. Issue 1 (March 2020) - Lupu, M L; Isopescu, D N; Cucoş, I; Antonescu, I; Maxineasa, S G; Baciu, I-R
Abstract: This paper presents the research, technologies and testing equipment developed for the energy plasma conversion of municipal waste in order to enhance energy-efficiency in the civil engineering domain. The purpose of this work is the environmentally friendly improving the efficiency of waste conversion processes by using controlled plasma decomposition reactors developed by the authors, which generate syngas, electrical and thermal energy which can be used in civil engineering.